Comparison of Oxytocin 10 IU Intravena Dilution of 10 ml Nacl 0.9% Bolus for 15 Seconds and 60 Seconds to Hemodynamics in Sectio Caesaria Patients with Spinal Anesthesia - Ricardo, Dion; Hanafie, Achsanuddin; Hamdi, Tasrif (CoinReads Media Prima, 2022)
Introduction: Caesarean section (SC) is defined as the birth of a baby through an incision in the abdomen (laparotomy) and uterus (hysterotomy). Spinal anesthesia is the choice for elective SC because it is considered effective and efficient considering its simple technique and ability to provide adequate surgical anesthesia, easy administration, faster onset, and safety. Spinal anesthesia also provides early skin to skin contact which increases maternal satisfaction although the hypotension risk is higher compared to epidural anesthesia which is countered by sympathomimetic vasopressors administration. The aim to research was to compare the administration of 10 IU oxytocin diluted in 10 cc of 0.9% NaCl for 15 seconds with 60 seconds on hemodynamics in sectio caesarean patients under spinal anesthesia. Method: This study used an RCT (Randomized Clinical Trial) design with double blind, meaning that neither the research subjects nor the observers were aware of the treatment or intervention given. The study sample was patients who underwent Sectio Caesaria at Haji Adam Malik General Hospital Medan, and the Universitas Sumatera Utara Hospital which fulfilled the inclusion and exclusion criteria. Results: It was found that there was not a significant difference in MAP values between the 15-second and 60-second bolus groups with p-values for the 1st, 3rd, 5th, and 10th minutes respectively 0.804, 0.692, 0.568 , 0.216, 0.754, and 0.390. In addition, it is known that there was a significant difference in pulse values between the 15-second and 60-second bolus groups at 1, 3, 5, 10 and 15 minutes, with the results of the p-value before, 1, 3, 5, 10, and 15 minutes are 0.509, 0.464, 0.805, 0.055, 0.475 and 0.857 respectively. In this study, no side effects were found in either group between 15 second and 60 second boluses. Conclusion: There were no significant hemodynamic changes in both test groups (15 second and 60 second boluses), at 1, 3, 5, 10 and 15 minutes.